Modelling investigation on fiber-on-fiber contacts for synthetic fibers - Nurul Hilwa Mohd Zini (2018)
Fiber is the main load bearer for engineering structures such as composites and rope. With characteristics such as superior mechanical strength, lightweight and flexible, synthetic fibers have replaced metals in many engineering applications. Due to its cylindrical body, contact between adjacent fibers can be subjected to various contact conditions, depending on the skew angle between the fibers. Fibers have large surface area-to-volume ratio, hence fiber contacts can be influenced by the surface forces such as adhesion. Adhesion in fiber contacts is governed by various factors such as surface roughness, intermolecular distance and the environment. There are various contact models available that can describe adhesive contacts. However, none of these models can describe adhesive elliptical contacts that are influenced by the angle between the contacting bodies and occur between materials that are neither rigid nor highly elastic. Hence, the development of an adhesive contact model for elliptical contacts is essential. In this thesis, the adhesive contact mechanics between fibers are investigated in the following aspects: 1. A contact model to describe the elliptical contact between cylindrical bodies with adhesion has been developed, for a range of skew angles. Realistic geometry assumptions on the load-dependent adhesive region have also been developed numerically. 2. An adhesion map for elliptical contacts has been constructed to guide the selection of suitable contact models. The construction is based on the aforementioned adhesive contact model. 3. The presence of adhesion has been shown to be significant in the contact between fibers in hierarchical structures.